γ−IFN production in human lymphocytes cultures for effect of the methanolic extracts from four ecotypes of Lepidium peruvianum, Chacón (Brassicaceae) - Alzamora, Libertad (2006)
The immunomodulatory activity was studied in function of the production of γ−IFN induced by the methanolic extracts (ME) of the white, black, red and purple ecotypes of Lepidium peruvianum, Chacón (at present Lepidium meyenii Walp.) maca, on cultures of human T lymphocytes obtained of periferic blood. After cultivating the lymphocytes with the respective ME of maca during 14 hours, only the ME of the purple ecotype induced the significant production of IFN−γ by Elispot quantified. The methanolic extract of the purple ecotype of maca possesses important immunostimulatory properties triggering the activation of the human T lymphocytes.